Dragons in a bag - Elliott, Zetta; B, Geneva (New York : Random House, 2018)
In Brooklyn, nine-year-old Jax joins Ma, a curmudgeonly witch who lives in his building, on a quest to deliver three baby dragons to a magical world, and along the way discovers his true calling.
School Library Journal starred, August 2018
Publisher's Weekly, August 2018
Kirkus Starred, August 2018
Booklist, August 2018
Horn Book, September 2018
5.2.
Keywords: African Americans -- Juvenile fiction; Magic -- Juvenile fiction; Dragons -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Juvenile fiction; African Americans -- Fiction; Magic -- Fiction; Dragons -- Fiction; Brooklyn (New York, N.Y.) -- Fiction; Fantasy fiction